A Comparative Standard Manufacturing procedure of Swarjika Kshara prepared from Ushtrapriya (Fagonia cretica Linn.) and Rudanti (Cressa cretica Linn.) (International Journal of Ayurveda and Pharma Research, 2025)
Swarjika Kshara is a significant alkaline formulation in Ayurveda, traditionally prepared using plants like Ushtrapriya (Fagonia cretica Linn.) and Rudanti (Cressa cretica Linn.). Classical references such as Rasatarangini and Ayurvediya Rasashastra describe the preparation of Kshara, while modern practices often substitute it with chemically synthesized sodium bicarbonate. The Ayurvedic Pharmacopeia of India (API) lacks specific standards for plant-origin Swarjika Kshara, necessitating a study to develop and standardize its manufacturing process. Aim: To develop a Standard Manufacturing Procedure (SMP) for Swarjika Kshara prepared from Ushtrapriya and Rudanti. Material and Methods: Three batches of Swarjika Kshara were prepared from Ushtrapriya and Rudanti following classical references. Pharmaceutical observations were recorded, and standardized batches were produced to validate uniformity. Yield percentages, ash content, and procedural differences were analyzed. Results: The study found significant differences in yield, with Rudanti (47.41%) producing more than double the Kshara compared to Ushtrapriya (18.46%). Both samples were successfully standardized, and uniform operative procedures were established. Conclusion: The study validated SMP for Swarjika Kshara from Ushtrapriya and Rudanti, ensuring consistency in production. The findings offer a foundation for large-scale manufacturing and future research, addressing the gap in API standards for plant-origin Swarjika Kshara.